PENGARUH STRUKTUR MODAL, PROFITABILITAS, LIKUIDITAS DAN AKTIVITAS TERHADAP PERINGKAT OBLIGASI PERUSAHAAN SWASTA NON KEUANGAN YANG DIPERINGKAT PT. PEFINDO TAHUN 2017-2021 - Manalu, Asdius; Silalahi, Donalson (LPPM Universitas Katolik Santo Thomas Medan, 2023)
This study was conducted to identify and explain the factors that influence bond ratings in private non-financial companies that PT Pefindo in 2017-2021. Factors that affect bond ratings include capital structure, profitability, liquidity, and activity. Based on the criteria, 85 bonds from 11 companies were obtained as samples. The sample data is pooled cross sections data obtained from the Indonesia Bond Market Directory, and the publication of 11 companies' annual financial reports. So the multiple linear regression analysis method was chosen as the method of testing the sample of this study. The results showed that capital structure (DER) has a positive effect on bond ratings. Profitability (ROE), liquidity (CR), activity (TATO) do not affect the bond rating. The capital structure effect is not in accordance with the hypothesis because the sample companies use more equity. The r square (R2) value is 0.181 or 1.81% of the effect of financial ratios on bond ratings in 2017-2021 by PT Pefindo. The beta value of capital structure of 0.389 times means that capital has the most influence on bond ratings in this research.